ACTUAL PROBLEMS OF JOINT MANAGEMENT OF WATER RESOURCES IN CENTRAL ASIA AND PROSPECTS FOR THEIR SOLUTION - FayzievaGulzoda Ulugbekovna (Scholar Express Journal, 2023)
Water resources play a crucial role in ensuring sustainable development. Without them, the already range of services that are provided on their basis will not be possible to reduce poverty and carry out the social transformations demanded by society
Keywords: Water; poverty; possible; society